IDENTIFYING GAPS AND NEEDS IN ENGLISH TEACHING PRACTICES FOR EFFECTIVE IMPLEMENTATION OF THE KURIKULUM MERDEKA AT SMA NEGERI 3 NGABANG - Siringo Ringo, Kezya Luna; Hafis, Maliqul; Sahrawi (Melekliterasi Press, 2025)
This study aims to identify the gaps and needs in implementing the Kurikulum Merdeka in English language teaching at the senior high school level. A qualitative method was employed, with data collected through observation, interviews, and documentation. The findings reveal several key gaps, including limited learning facilities, insufficient teacher understanding of the curriculum and differentiated assessment, low student engagement and readiness, and challenges in aligning assessments with Learning Outcomes. Additionally, the use of technology and teacher training remain suboptimal. This study recommends targeted professional development, improved access to learning resources, and stronger institutional support to ensure the effective implementation of Kurikulum Merdeka.